1981
DOI: 10.1530/jrf.0.0610289
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of the aetiology, diagnosis and treatment of infertility in the bitch

Abstract: The nature of the infertility in 19 bitches was investigated: 10 animals were considered to be normal on the basis of their sexual behaviour, vaginal cytology and plasma oestrogen and progesterone concentrations. Successful conception and whelping occurred for 6 of the 10 bitches. The previous apparent infertility was probably attributable to defective mating management by the owners. Although follicular development and ovulation occurred in 4 of the remaining bitches, oestrus was not exhibited: AI resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In spite of normal oestradiol and progesterone values some bitches do not show overt behavioural signs and may be shy and refuse to accept coitus (Arthur, Noakes & Pearsson, 1982;Linde unpubl. ;Renton et al, 1981;Wildt el al., 1981). This indicates a psychological aberration rather than a hormonal one.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of normal oestradiol and progesterone values some bitches do not show overt behavioural signs and may be shy and refuse to accept coitus (Arthur, Noakes & Pearsson, 1982;Linde unpubl. ;Renton et al, 1981;Wildt el al., 1981). This indicates a psychological aberration rather than a hormonal one.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the stage of the oestrous cycle affects response to hormonal treatment including eCG (Renton et al . ). Actually, we observed a variety of physiological and endocrinological changes after hormonal treatment in each bitch, but follicular growth was observed in all bitches and new follicular growth appeared from 2 to 8 days after the eCG/hCG administration.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, oestrous induction is rarely used as a treatment for primary anoestrus, which is defined by the absence of an oestrous cycle by 24 months of age (Renton et al 1981;Gobello et al 2002).…”
Section: Introductionmentioning
confidence: 99%